Вы находитесь на странице: 1из 3

# .

A f (x) a
( x a )

A f (x)

( x )
(x)

lim f ( x) = A

f (x)

lim f ( x ) =

lim f ( x) = A
x a

lim ( x) = 0
xa

xa

f ( x ) lim ( x)
lim
x a
xa
( )

(
)

( )

xa

x a

x a

xa

x a

x a

f ( x)
f ( x ) lim
= x a
; lim ( x ) 0
xa ( x)
x a
lim ( x)

lim

x a

## lim(C f ( x)) = C lim f ( x)

x a

x a

lim( f ( x )) n = lim f ( x)
xa

x a

sin x
lim
=1
x 0
x

sin kx
tgx
=k
=1
2. lim
x

0
x
x
tgkx
arcsin x
arctgx
= k 4. lim
= 1 5. lim
=1
3. lim
x 0
x

0
x

0
x
x
x
1. lim
x 0

1
lim1 + = e , e = 2,718281...
x
x

1. lim(1 + x )
x 0

1
x

k
= e 2. lim1 + = e k
x
x

( )
(x) (x)

(x) x a ,
1
x a .
( x)

( x) = 0 lim ( x) = 0 ,
lim
xa
xa
lim( ( x) ( x) ) = 0
xa

( x) = 0 f ( x) < M ,
lim
xa
lim f ( x ) ( x ) = 0
xa

( x) = 0 , lim
lim
xa
xa

1
=
( x)

( )
lim
( x) =
xa f ( x ) = lim
xa

lim( f ( x) ( x) ) = .

xa

f ( x ) = ( x) < M ,
lim
xa

lim f ( x) ( x) =

x a
x

a
f
(x
)
1

,
f ( x ) = , lim
=0
lim
x

a
x

a
1
f ( x)

x a .
f ( x)

1.

## sin x x tgx arcsin x arctgx ln(1 + x) e x 1

2. 1 cos x

x
x2
; 3. (1 + x) k 1 kx ; 4. a x 1 x ln a ;5. n 1 + x 1 ;6. log a (1 + x ) x log a e
n
2

y = f (x)

= a

y = f (x) ,

lim f ( x) lim f ( x)
x a + 0
x a 0

y = kx + b

y = f (x) ,
lim ( f ( x ) ( kx + b) ) = 0

f ( x)
( f ( x) kx ) = b
lim
= k xlim

x x

y = f (x)

l

y = f (x) ,

y = b

y = f (x) ,
lim f ( x) = b

y = f (x)

## Нижнее меню

### Получите наши бесплатные приложения

Авторское право © 2021 Scribd Inc.